Immunogenicity and safety of one versus two doses of tetravalent dengue vaccine in healthy children aged 2–17 years in Asia and Latin America: 18-month interim data from a phase 2, randomised, placebo-controlled study. Issue 2 (February 2018) - Sáez-Llorens, Xavier; Tricou, Vianney; Yu, Delia; Rivera, Luis; Jimeno, José; Villarreal, Ana Cecilia; Dato, Epiphany; Mazara, Sonia; Vargas, Maria; Brose, Manja; Rauscher, Martina; Tuboi, Suely; et al.
Summary: Background: Development of vaccines that are effective against all four dengue virus serotypes (DENV-1–4) in all age groups is important. Here, we present 18-month interim data from an ongoing study undertaken to assess the immunogenicity and safety of Takeda's tetravalent dengue vaccine (TDV) candidate over 48 months in children living in dengue-endemic countries. Methods: We undertook a phase 2, multicentre, randomised, double-blind, placebo-controlled study at three sites in the Dominican Republic, Panama, and the Philippines. We randomly assigned children aged 2–17 years to receive either two TDV doses 3 months apart (group 1), one TDV dose (group 2), one TDV dose and a booster dose 1 year later (group 3), or placebo (group 4). We did the randomisation (1:2:5:1) using an interactive web response system stratified by age. The primary endpoint of this 18-month interim analysis was DENV serotype-specific antibody geometric mean titres (GMTs) in the per-protocol immunogenicity subset on days 1, 28, 91, 180, 365, 393, and 540. Secondary safety endpoints were the proportions of participants with serious adverse events and with virologically confirmed dengue in the safety set, and solicited and unsolicited adverse events in the immunogenicity subset. This trial is registered with ClinicalTrials.gov, number NCT02302066 . Findings: Between Dec 5, 2014, and Feb 13, 2015, 1800 children were randomly assigned to group 1 (n=201), group 2 (n=398), group 3 (n=1002), and group 4 (n=199). 1794 participants received at least one dose of TDV or placebo (safety set), of whom 562 participated in the immunogenicity subset and 509 were included in the per-protocol set. Antibody titres remained elevated 18 months after vaccination in all TDV groups. At day 540, in groups 1, 2, 3, and 4, respectively, DENV-1 GMTs were 476 (95% CI 286–791), 461 (329–647), 1056 (804–1388), and 92 (49–173); DENV-2 GMTs were 1212 (842–1744), 1242 (947–1628), 1457 (1182–1796), and 177 (93–337); DENV-3 GMTs were 286 (171–478), 298 (205–433), 548 (411–730), and 78 (44–137); and DENV-4 GMTs were 98 (65–150), 102 (75–139), 172 (133–222), and 33 (21–52). Limited differences in GMTs were observed between groups 1 and 2 (in which participants received one and two doses of TDV, respectively). In baseline-seronegative participants, a 1-year booster clearly increased GMTs. Vaccine-related unsolicited adverse events occurred in 14 (2%) of 562 participants, but no vaccine-related serious adverse events arose. Symptomatic, virologically confirmed dengue was recorded in 21 (1·3%) of 1596 participants vaccinated with TDV compared with nine (4·5%) of 198 placebo recipients. Interpretation: TDV was well tolerated and immunogenic against all four dengue serotypes, irrespective of baseline dengue serostatus. These data provide proof of concept for TDV and support the ongoing phase 3 efficacy assessment of two doses 3 months apart. Funding: Takeda Vaccines.